2021
DOI: 10.1371/journal.pone.0255783
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension induced by pregnancy and neonatal outcome: Results from a retrospective cohort study in preterm under 34 weeks

Abstract: Objective The present study seeks to assess the impact of gestational hypertensive disorders on premature newborns below 34 weeks and to establish the main morbidities and mortality in the neonatal period and at 18 months. Materials and methods A retrospective observational study was carried out with 695 premature newborns of gestational age (GA) between 24 and 33 weeks and 6 days, born alive in the Neonatal ICU of Brasília’s Mother and Child Hospital (HMIB), in the period from January 1, 2014, to July 31, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 35 publications
1
7
0
1
Order By: Relevance
“…Neonates whose mothers had GDM and preeclampsia were more likely to develop respiratory disorders. Although this view has been widely accepted in several studies [4,[20][21][22] , an increasing number of opposing opinions have been proposed [23][24][25][26] . MH has received little attention for neonatal respiratory issues because it mainly affects the nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…Neonates whose mothers had GDM and preeclampsia were more likely to develop respiratory disorders. Although this view has been widely accepted in several studies [4,[20][21][22] , an increasing number of opposing opinions have been proposed [23][24][25][26] . MH has received little attention for neonatal respiratory issues because it mainly affects the nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that the percentile on the Fenton curve at birth is an important predictor of EUGR [23]. In addition, gestational hypertension can increase the need for emergency cesarean section [24], which is an independent risk factor for low Apgar score [25]. These infants are often born sick and even require mechanical ventilation, leading to an increased risk of BPD and EUGR.…”
Section: Discussionmentioning
confidence: 99%
“…The first experiment was with grounding without tools, where the researcher's feet directly touched the ground/grass [4]. Figure 2 is leg-wearing rubber footwear (not grounding); the skin voltage reaches 274.8 millivolts.…”
Section: Research Instrumentsmentioning
confidence: 99%
“…The incidence of hypertension in pregnancy in Indonesia is 24% the cause of maternal death (1) and is a significant cause of morbidity and mortality of mothers and infants worldwide (2). Hypertension in pregnancy leads to preeclampsia and eclampsia (seizures) (3); it is also the highest cause of neonatal death, namely the leading cause of low birth weight (4,5). Research reports that Earthing can reduce hypertension by reducing blood viscosity (6), a major factor in cardiovascular disease (7,8).…”
Section: Introductionmentioning
confidence: 99%